Strategie cognitive per l'autoregolazione dell'apprendimento e motivazione allo studio. Costruzione di Profili medi del funzionamento cognitivo e dell'assetto motivazionale per la prevenzione del drop-out - Valeria Biasi; Conny De Vincenzo; Nazarena Patrizi (LED Edizioni Universitarie, 2018)
The article presents the results of an empirical longitudinal study focusing on the cognitive and motivational factors that influence the risk of drop-out. Thanks to a previous empirical contribution (Biasi, De Vincenzo, & Patrizi, 2017) conducted through an online questionnaire with 2328 students of Roma Tre University, we identified as predictors of drop-out some inadequate cognitive strategies, lack of motivation (or «amotivation») and low levels of school self-efficacy. In order to identify the consistency over time of the relationship between these cognitive and motivational factors, we carried out a year-long longitudinal study aimed at investigating the academic experience of a self-selected sample of 68 students who completed three successive tests. The data showed that the greater the risk of drop-out, the lower the scores obtained by students, over a year, in cognitive strategies of «practice» and «monitoring» of knowledge. Students with a high risk of drop-out also showed a poor connection of new knowledge to the knowledge they already possessed. Moreover, it was confirmed that higher drop-out risk scores correlate with a high level of «amotivation» and «external» motivation scores, and with a low level of «Intrinsic» motivation: persistence over time was also highlighted. Some average «Profiles of cognitive functioning and motivational structure» were devised, useful for individualized guidance or orientation interventions geared to identifying which cognitive strategies can be reinforced in order to favor learning and - during re-orientation - to take into account the level of coherence of student motivation with the chosen study track.